Tunable multi-electron redox polyoxometalates for decoupled water splitting driven by sunlight - Li-Ping Cui; Shu Zhang; Yue Zhao; Xin-Yue Ge; Le Yang; Ke Li; Liu-Bin Feng; Ren-Gui Li; Jia-Jia Chen (Nature Communications)
Abstract It remains a great challenge to explore redox mediators with multi-electron, suitable redox potential, and stable pH buffer ability to simulate the natural solar-to-fuel process. In this work, we present a defect engineering strategy to design soluble multi-electron redox polyoxometalates mediators to construct a photocatalysis-electrolysis relay system to decouple H2 and O2 evolution in solar-driven water splitting. The appropriate use of vanadium atoms to replace tungsten in the Dawson-type phosphotungstate successfully regulated the redox properties of the molecular clusters. Specifically, the single vanadium substitution structure (P2W17V) possesses 1-electron redox active and sequential proton-electron transfer behavior, while the tri-vanadium substituted cluster (P2W15V3) exhibits 3-electron redox active and cooperative proton electron transfer behavior. Based on the developed multi-electronic redox mediator with pH buffering capacity, suitable redox potential (0.6 V), and fast electron exchange rate, we build a photocatalysis-electrolysis relay water splitting system. This system allows for high capacity of solar energy storage through photocatalytic O2 evolution using BiVO4 photocatalyst and stable H2 production with a high Faraday efficiency of over 98.5% in the electrolysis subsystem.